1986
DOI: 10.1128/jb.167.1.299-304.1986
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and modification of exogenous phosphatidylcholines by mycoplasmas

Abstract: The uptake and modification of exogenous phosphatidylcholine (PC) by several Mycoplasma and Spiroplasma species was investigated. While in most Mycoplasma species and in all Spiroplasma species tested the PC appears to be incorporated unchanged from the growth medium, the PC of M. gallisepticum, M. pulmonis, and M. pneumoniae was disaturated PC, apparently formed by modification of l-saturated-2-unsaturated PC from the growth medium. The modification of the exogenous PC by M. gallisepticum was inhibited by chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Putative mimics affecting host lipid metabolism include detected pathogen counterparts of human cholinephosphotransferase, PCTP like protein, fukutin, acyltransferases, phospholipase A2, carnitine O-palmitoyltransferase, and sterol reductase (Table 3). For example, Mycobacterium pneumonia is known to incorporate host lipids (e.g., phosphatidylcholine), 68 and has been shown to modulate host sphingolipid metabolism 45 . A human-like carnitine O-palmitoyltransferase (CPT) was detected in Mycobacterium pneumonia , which may play a role in these functions 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Putative mimics affecting host lipid metabolism include detected pathogen counterparts of human cholinephosphotransferase, PCTP like protein, fukutin, acyltransferases, phospholipase A2, carnitine O-palmitoyltransferase, and sterol reductase (Table 3). For example, Mycobacterium pneumonia is known to incorporate host lipids (e.g., phosphatidylcholine), 68 and has been shown to modulate host sphingolipid metabolism 45 . A human-like carnitine O-palmitoyltransferase (CPT) was detected in Mycobacterium pneumonia , which may play a role in these functions 44 .…”
Section: Resultsmentioning
confidence: 99%
“…It might be argued that acyl chains donated to the proteins by polar lipids of the serum fraction, known to be possible in M. capricolum (8), have escaped our detection since they are not labeled. However, exogenously incorporated polar lipids seem to be metabolically inert in spiroplasmas, whereas this is not the case in mycoplasmas (11,35).…”
Section: Resultsmentioning
confidence: 99%
“…urealyticurn possessed endogenous phospholipase Al, A2 and C activity which was essentially membrane-bound (De Silva & Quinn, 1991). Low levels of membrane-bound phospholipase A activity were also present in M. gallisepticurn; this activity was increased fourfold by detergents and it was suggested that in intact cells activation was brought about by soluble regulatory proteins (Rottem et al, 1986). Phospholipase A2 has been demonstrated in culture supernatants of M. mycoides and Ac.…”
Section: Catabolism Of Lipidsmentioning
confidence: 96%